Culture-bound addictions among low income workers of Karachi, Pakistan - Salman, Sara; Khalil, Rehana; Gul, Saadia (International Journal of Research in Medical Sciences, 2017)
Background: The self-efficacy of individuals is influenced by experiences in the community, in the workplace, and in broader civil society, all of which exert a collective influence on attitudes and behaviors. The low-income population is more likely to engage in the use of culture bound addictive substances which include tobacco, gutkha, betel nut/areca nut, alcohol and caffeine. The objective of the study was to identify the type of culture-bound substances used by low-income workers and also to determine the prevalence of substance use among low-income workers, in Karachi, Pakistan. Methods: A cross sectional study was carried out in Karachi, Pakistan. Trained interviewers used a semi-structured questionnaire to interview 707 workers to collect information on socio-demographic characteristics, and addiction history. The data were analyzed using SPSS version 18. Results: Majority (26.4%) of the participants were aged between 26 and 30 years. More than one-third (35.1%) were educated up to secondary level only. Half of the sample (50.8) had 6 to 10 house hold members whereas only one member was employed among 34.8% of the respondents. 39.5% participants reported a household income between Rs11000 and Rs 20000 per month. Half of the sample (50.4%) reported some sort of substance use in their daily routine. A significant number (39.5%) of workers were found to be addicted to tobacco, gutkha or betel nut alone, while another 10.5% were using these substances in combination. Conclusions: Addiction to culture bound substances is prevalent among 50% of the low income workers of Karachi, Pakistan. The common culture bound addiction substances the workers were found to be using were tobacco, ghutka and betel nut. The findings of the present study cannot be generalized due to the limited sample. Still, the study provides evidence of this unhealthy behavior among workers that not only affects their productivity but plays a vicious role in poverty and poor health cycle. Future research should direct attention toward workers' health and working conditions to formulate effective public health interventions to reduce the risky behavior among low income workers. Moreover, there is a need to develop health education programs to create awareness and empowerment among low-income workers to prevent substance use.